Rna-Seq Analysis and Transcriptome Assembly of Salicornia Neei Reveals a Powerful System for Ammonium Detoxification - Maldonado-Soto, J (Pontificia Universidad Catolica de Valparaiso, 2022)
Background: Salicornia neei is a halophyte plant that has been proposed for use in the phytoremediation of the saline wastewater generated by land-based aquaculture. To identify the molecular mechanisms related to ammonium response, we analyzed the transcriptome of S. neei in response to growth in saline water containing 3 mM ammonium. Results: The RNA sequencing generated a total of 14,680,108 paired-end reads from the control and stressed conditions. De novo assembly using the CLC Genomic Workbench produced 86,020 transcripts and a reference transcriptome with an N50 of 683 base pair. A total of 45,327 genes were annotated, representing 51.2% of the contig predicted from de novo assembly. As regards differentially expressed genes, a total of 9,140 genes were differentially expressed in response to ammonium in saline water; of these, 7,396 could be annotated against functional databases. The upregulated genes were mainly involved in cell wall biosynthesis, transmembrane transport and antiporter activities, including biological Kyoto Encyclopedia of Genes and Genomes, pathways linked to the biosynthesis of secondary metabolites, plant hormone signal transduction, autophagy, and nitrogen metabolism. In addition, a set of 72 genes was directly involved in ammonium metabolism, including glutamine synthetase 1, glutamate synthase 1, and ferredoxin-dependent glutamate synthase chloroplastic. Conclusions: Our results support the hypothesis that an ammonium detoxification system mediated by glutamine and glutamate synthase was activated in S. neei when exposed to ammonium and saline water. The present transcriptome profiling method could be useful when investigating the response of halophyte plants to saline wastewater from land-based aquaculture. This manuscript includes an interactive 360 degree video, supplementary to the materials and methods section. To view the video correctly, it is necessary to scroll through the screen to navigate across the laboratory where you will find 6 interactive points. For an immersive experience a head-mounted display can be used. Please, visit this URL: http://ejbiotechnology.info/public/360view/2022/VTPGALLARDO_1v3/index.htm. How to cite: Díaz-Silva M, Maldonado J, Veloso P, et al. RNA-seq analysis and transcriptome assembly of Salicornia neei reveals a powerful system for ammonium detoxification. Electron J Biotechnol 2022;58. https://doi.org/10.1016/j.ejbt.2022.05.003 © 2022